Shikhara (superstructure) of Mahanaleshwar Temple - Temples of India Project Team (Jio Institute, 2024)
Seen here is the south-facing elevation of the shikhara (superstructure) of the Mahanaleshwar Temple. The front side of the shikhara has an elaborate shukanasa (an ornamented projection over the entrance of the sanctum), with a lion sculpture on top of it. The shukanasa has a niche at its centre and above it is a chaitya (horseshoe-shaped) medallion. The mouldings of the shukanasa are similar to the plinth mouldings of the temple. A noteworthy aspect is the three bhumija aedicules on each side of the shikhara.